If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3t-3=7
We move all terms to the left:
3t-3-(7)=0
We add all the numbers together, and all the variables
3t-10=0
We move all terms containing t to the left, all other terms to the right
3t=10
t=10/3
t=3+1/3
| -11/2.75=x | | -4.5*(-6.2)=b | | -4.5*(-6.2)=b | | 15x+9=9+25x | | 2+0.75x=1+.80x | | 3^(x+4)=6^x | | G(x)=5x(2 | | -12-b=-4 | | -0.80(10x)=36 | | 183-8=25x | | 183-8=25x | | 183-8=25x | | 183-8=25x | | 10+7y=8y | | 3x2x=-15 | | 3x2x=-15 | | 3x2x=-15 | | 3x2x=-15 | | 3x2x=-15 | | 3x2x=-15 | | 3x2x=-15 | | 3x2x=-15 | | 10y-31=67 | | 8x+9x=+3 | | 8x+9x=+3 | | 8x+9x=+3 | | 8x+9x=+3 | | 10f-31=67 | | 10f-31=67 | | 6x+175=3x127 | | 6x+175=3x127 | | a^2+1521=1296 |